Light emitting device and method of fabricating the same
Patent Information
- Application Number
- CN202011636859.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-31
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2040-12-31
AI Technical Summary
[0004]本申请的目的在于提供一种发光器件及其制备方法,旨在一定程度上解决电子传输层与相邻功能层之间的界面融合差,影响电子注入迁移效率,易形成电荷累积的问题
[0013] The method for fabricating a light-emitting device provided in the first aspect of this application involves, on the one hand, fabricating a multilayered composite electron transport layer in the device, comprising both a metal oxide sub-transport layer with high electron mobility and an organic sub-transport layer with a wide range of energy level modulation. This allows the composite electron transport layer to simultaneously possess high electron mobility and energy level matching characteristics, enabling flexible modulation of the energy levels and electron mobility of the electron transport layer and optimizing the electron and hole injection and recombination efficiency within the light-emitting layer. On the other hand, by subjecting the light-emitting device to ultraviolet light irradiation, electrons of O in the Nth sub-electron transport layer containing the metal oxide transport material are excited and form complexes with active metal elements such as Zn in the adjacent quantum dot light-emitting layer (QD), making the QD-ETL interface more integrated and facilitating electron injection into the interior of the light-emitting layer. Furthermore, the coordination of electrons of O in the metal oxide with the quantum dot material increases the bonding defects within the transport layer, thereby improving the electron mobility within the transport layer. In addition, the formed complexes and metal oxide transport materials have a strong absorption effect on UV light, which activates bonding electrons, promotes crystal re-growth, reduces physical structural defects and surface roughness inside the transport layer, makes the QD-ETL interface more tightly and stably bonded, reduces interface gaps, lowers the potential barrier between functional layers, is more conducive to electron injection, reduces charge accumulation in the interface layer, reduces material aging rate, and improves device life.
Smart Images

Figure CN114695820B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of display device technology, and in particular relates to a light-emitting device and its preparation method. Background Technology
[0002] Quantum dots are nanocrystalline particles with radii smaller than or close to the Bohr exciton radius, typically with a particle size between 1 and 2. Quantum dots exhibit quantum confinement effects, emitting fluorescence upon excitation. Furthermore, they possess unique luminescent properties such as broad excitation peaks, narrow emission peaks, and tunable emission spectra, making them promising for applications in optoelectronics. Quantum dot light-emitting diodes (QLEDs) are a rapidly emerging display technology in recent years. QLEDs use colloidal quantum dots as the light-emitting layer, introducing this layer between different conductive materials to obtain light of the desired wavelength. QLEDs offer advantages such as high color gamut, self-emission, low start-up voltage, and fast response speed.
[0003] Currently, OLED devices typically employ multi-layered structures to balance carrier injection, with quantum dot emissive layers often utilizing core-shell quantum dot nanomaterials. In quantum dot LEDs, the organic surface ligands and intricate core-shell structure of the quantum dot nanoparticles limit their annealing temperature, resulting in a high interface roughness for the quantum dot layer. Furthermore, the annealing temperature of the quantum dot layer also restricts the annealing temperature of the adjacent electron transport layer (ETL), making it difficult for the electron transport material to reach a suitable crystallization temperature. This leads to discontinuities in the internal structure of the electron transport layer, reducing electron mobility and increasing interface roughness. The high interface roughness between the quantum dot emissive layer and the electron transport layer affects the continuity of carrier injection into the quantum dot emissive layer, resulting in low injection efficiency and reduced carrier injection performance. Moreover, charge accumulation centers easily form at the interface gaps, accelerating material aging and severely impacting device lifetime. Summary of the Invention
[0004] The purpose of this application is to provide a light-emitting device and its fabrication method, which aims to solve to some extent the problem of poor interface fusion between the electron transport layer and adjacent functional layers, affecting electron injection migration efficiency and easily leading to charge accumulation.
[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:
[0006] In a first aspect, this application provides a method for fabricating a light-emitting device, comprising the following steps:
[0007] Obtain a substrate with a deposited cathode;
[0008] A first sub-electron transport layer to an Nth sub-electron transport layer are sequentially prepared on the cathode surface away from the substrate to form an electron transport layer.
[0009] A quantum dot light-emitting layer and an anode are sequentially fabricated on the surface of the Nth sub-electron transport layer away from the cathode to obtain a light-emitting device;
[0010] The light-emitting device is subjected to ultraviolet light irradiation treatment;
[0011] Wherein, at least one sub-electron transport layer in the electron transport layer includes an organic transport material, and at least the Nth sub-electron transport layer includes a metal oxide transport material, where N is a positive integer greater than or equal to 2.
[0012] Secondly, this application provides a light-emitting device, which is manufactured by the method described above.
[0013] The method for fabricating a light-emitting device provided in the first aspect of this application involves, on the one hand, fabricating a multilayered composite electron transport layer in the device, comprising both a metal oxide sub-transport layer with high electron mobility and an organic sub-transport layer with a wide range of energy level modulation. This allows the composite electron transport layer to simultaneously possess high electron mobility and energy level matching characteristics, enabling flexible modulation of the energy levels and electron mobility of the electron transport layer and optimizing the electron and hole injection and recombination efficiency within the light-emitting layer. On the other hand, by subjecting the light-emitting device to ultraviolet light irradiation, electrons of O in the Nth sub-electron transport layer containing the metal oxide transport material are excited and form complexes with active metal elements such as Zn in the adjacent quantum dot light-emitting layer (QD), making the QD-ETL interface more integrated and facilitating electron injection into the interior of the light-emitting layer. Furthermore, the coordination of electrons of O in the metal oxide with the quantum dot material increases the bonding defects within the transport layer, thereby improving the electron mobility within the transport layer. In addition, the formed complexes and metal oxide transport materials have a strong absorption effect on UV light, which activates bonding electrons, promotes crystal re-growth, reduces physical structural defects and surface roughness inside the transport layer, makes the QD-ETL interface more tightly and stably bonded, reduces interface gaps, lowers the potential barrier between functional layers, is more conducive to electron injection, reduces charge accumulation in the interface layer, reduces material aging rate, and improves device life.
[0014] The light-emitting device provided in the second aspect of this application employs a multi-layered composite structure for its electron transport layer, comprising both a metal oxide sub-transport layer with high electron mobility and an organic sub-transport layer with a wide range of energy level modulation. This allows the electron transport layer to simultaneously possess high electron mobility and flexibility in energy level matching, optimizing the electron-hole recombination efficiency within the light-emitting layer. Furthermore, after ultraviolet irradiation, electrons from the O in the metal oxide transport material of the Nth sub-electron transport layer are excited and form complexes with active metal elements such as Zn in the quantum dot light-emitting layer. Simultaneously, the metal oxide material exhibits good fusion with the cathode after ultraviolet excitation. This reduces internal physical structural defects and surface roughness within the electron transport layer, resulting in high electron transport mobility. Additionally, the interface between the quantum dot light-emitting layer and the electron transport layer is tightly bonded, leading to high electron injection efficiency, avoiding charge accumulation at the functional layer interface, and resulting in good device stability and a long lifespan. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a schematic flowchart of the fabrication method of the light-emitting device provided in the embodiments of this application;
[0017] Figure 2 This is a schematic diagram of the structure of the light-emitting device provided in the embodiments of this application;
[0018] Figure 3 This is a schematic diagram of the positive structure of a quantum dot light-emitting diode provided in an embodiment of this application;
[0019] Figure 4 This is a schematic diagram of the inversion structure of a quantum dot light-emitting diode provided in an embodiment of this application;
[0020] Figure 5 These are efficiency curves of quantum dot light-emitting diodes provided in Embodiments 1 and 4, Comparative Example 1 and Comparative Example 2 of this application;
[0021] Figure 6 These are current density-voltage curves of quantum dot light-emitting diodes provided in Embodiments 1, 4, Comparative Example 1, and Comparative Example 2 of this application;
[0022] Figure 7 These are brightness curves of quantum dot light-emitting diodes provided in Embodiments 1, 4, Comparative Example 1, and Comparative Example 2 of this application. Detailed Implementation
[0023] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0024] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.
[0025] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0026] It should be understood that, in the various embodiments of this application, the sequence numbers of the above processes do not imply a sequential order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application. The terminology used in the embodiments of this application is for the purpose of describing specific embodiments only and is not intended to limit this application. The singular forms "a" and "the" used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0027] As attached Figure 1 As shown, the first aspect of this application provides a method for fabricating a light-emitting device, comprising the following steps:
[0028] S10. Obtain a substrate with a deposited cathode;
[0029] S20. The first sub-electron transport layer to the Nth sub-electron transport layer are sequentially prepared on the cathode surface away from the substrate to form an electron transport layer;
[0030] S30. A quantum dot light-emitting layer and an anode are sequentially fabricated on the surface of the Nth sub-electron transport layer away from the cathode to obtain a light-emitting device;
[0031] S40. The light-emitting device is subjected to ultraviolet light irradiation treatment;
[0032] Wherein, at least one sub-electron transport layer in the electron transport layer includes an organic transport material, and at least the Nth sub-electron transport layer includes a metal oxide transport material, where N is a positive integer greater than or equal to 2.
[0033] The method for fabricating a light-emitting device provided in the first aspect of this application involves, on the one hand, fabricating a multilayered composite electron transport layer in the device, comprising both a metal oxide sub-transport layer with high electron mobility and an organic sub-transport layer with a wide range of energy level modulation. This allows the composite electron transport layer to simultaneously possess high electron mobility and energy level matching characteristics, enabling flexible modulation of the energy levels and electron mobility of the electron transport layer and optimizing the electron and hole injection and recombination efficiency within the light-emitting layer. On the other hand, by subjecting the light-emitting device to ultraviolet light irradiation, electrons of O in the Nth sub-electron transport layer containing the metal oxide transport material are excited and form complexes with active metal elements such as Zn in the adjacent quantum dot light-emitting layer (QD), making the QD-ETL interface more integrated and facilitating electron injection into the interior of the light-emitting layer. Furthermore, the coordination of electrons of O in the metal oxide with the quantum dot material increases the bonding defects within the transport layer, thereby improving the electron mobility within the transport layer. In addition, the formed complexes and metal oxide transport materials have a strong absorption effect on UV light, which activates bonding electrons, promotes crystal re-growth, reduces physical structural defects and surface roughness inside the transport layer, makes the QD-ETL interface more tightly and stably bonded, reduces interface gaps, lowers the potential barrier between functional layers, is more conducive to electron injection, reduces charge accumulation in the interface layer, reduces material aging rate, and improves device life.
[0034] In some embodiments, after preparing the quantum dot light-emitting layer, the method further includes the steps of: preparing a hole transport layer on the surface of the quantum dot light-emitting layer opposite to the electron transport layer, and preparing an anode on the surface of the hole transport layer opposite to the quantum dot light-emitting layer.
[0035] In some embodiments, a schematic diagram of the structure of the light-emitting device prepared according to the present application is shown in the attached figure. Figure 2 As shown, from top to bottom, it includes an anode, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer (from top to bottom, it includes the Nth sub-electron transport layer, the (N-1)th sub-electron transport layer... the first sub-electron transport layer) and a cathode, wherein the Nth sub-electron transport layer closest to the quantum dot light-emitting layer is a metal oxide layer.
[0036] In some embodiments, in the fabricated light-emitting device, the first sub-electron transport layer near the cathode and the Nth sub-electron transport layer near the quantum dot light-emitting layer each independently contain metal oxide transport materials, where N is a positive integer greater than or equal to 3, preferably less than or equal to 9. A value for N that is too large will result in an excessively thick electron transport layer, which is detrimental to electron transport. The optoelectronic device fabricated in this application, through ultraviolet light irradiation, promotes the coordination of the metal oxide transport material in the Nth sub-electron transport layer with the active metal element in the quantum dot, and simultaneously promotes the coordination of the metal oxide transport material in the first sub-electron transport layer with the metal element in the metal cathode, improving the fusion between the QD-ETL and ETL-cathode interfaces, and further facilitating electron injection.
[0037] In some embodiments, the particle size of the metal oxide transport material in the Nth electron transport layer is 2–4 nm. Smaller particle sizes result in a larger specific surface area and higher surface activity, making it easier for the metals in the quantum dots to interact with each other under ultraviolet light irradiation, forming a superior QD-ETL interface. Furthermore, the wider band gap of the smaller particle sizes reduces exciton quenching in the light-emitting layer, thus improving device efficiency.
[0038] In some embodiments, the electron transport layer includes at least one sub-electron transport layer of metal oxide transport material with a particle size of 4 to 8 nm. Metal oxides with this particle size have high electron mobility, which is beneficial for electron injection into the light-emitting layer. They are also easier to disperse in solution and have better film-forming properties.
[0039] In some embodiments, the electron transport layer includes at least one sub-electron transport layer with a metal oxide transport material particle size of 4–8 nm, and the metal oxide transport material in the Nth sub-electron transport layer has a particle size of 2–4 nm. Since small-particle-size metal oxides have relatively low electron mobility, affecting electron injection, and exhibit relatively poor stability and film formation performance, thus reducing device performance, this application employs a combination of QD / 2–4 nm small-particle-size metal oxides / 4–8 nm large-particle-size metal oxides to enable the electron transport layer to possess characteristics such as high electron migration and injection efficiency, film formation stability, and QD-ETL interface compatibility, thereby improving device performance.
[0040] In some embodiments, the quantum dot emitting layer comprises a core-shell quantum dot material, with the outer shell containing zinc. Since most current quantum dot synthesis utilizes elements from groups II-VI, Zn exhibits better lattice matching and band gap compatibility with group VI elements, enabling coverage of the entire visible light spectrum. Furthermore, the zinc-containing outer shell of the quantum dot material offers suitable chemical reactivity, high flexibility and controllability, a wide band gap, good exciton binding, high quantum efficiency, and good water and oxygen stability. Additionally, zinc exhibits better and more stable electron coordination with O. Upon UV irradiation, the electrons of O in the metal oxide transport material of the electron transport layer are excited, readily forming a complex with Zn in the QD, namely the ZnO complex. The formation of the ZnO complex facilitates electron injection, improving the electron mobility in the electron transport layer. Meanwhile, ZnO complexes have a strong absorption effect on ultraviolet light wavelengths, which is conducive to activating bonding electrons, enabling the crystal in the ETL to grow again, reducing internal physical structure defects and surface roughness of the ETL, facilitating electron injection, reducing electron accumulation, slowing down material aging, and improving device lifespan.
[0041] In some embodiments, the outer shell of the quantum dot material comprises an alloy material formed from at least one or two of ZnS, ZnSe, ZnTe, CdZnS, and ZnCdSe. These outer shell materials all contain zinc, which is highly reactive and has a good coordination effect with excited O electrons in electron transport materials.
[0042] In some embodiments, the ultraviolet light irradiation treatment step includes: using ultraviolet light with a wavelength of 250–420 nm and a light density of 10–300 mJ / cm². 2 Under these conditions, the light-emitting device is irradiated for 10–60 minutes. The ultraviolet irradiation treatment conditions described in this embodiment can effectively promote the coordination of O atoms in the metal oxide transport material of the ETL with elements such as zinc in the quantum dot shell layer. This not only optimizes the interface gap between the electron transport layer and the quantum dot light-emitting layer and cathode, improving electron migration and injection efficiency, but also significantly increases bonding within the ETL, promoting internal crystal regrowth, reducing internal crystal structure defects and surface roughness, and improving electron mobility.
[0043] In some embodiments, the ultraviolet (UV) irradiation treatment conditions include: conducting the treatment in an environment with an H₂O content of less than 1 ppm and a temperature of 80–120°C. In this application embodiment, UV irradiation treatment is conducted in an environment with an H₂O content of less than 1 ppm and a temperature of 80–120°C to avoid excessive moisture content in the environment causing hydrolysis of the quantum dot material surface during the irradiation process, which would affect the material's performance. Simultaneously, the heating environment of 80–120°C is beneficial for further promoting the bonding of excited O electrons with zinc ions and also for activating the bonding electrons.
[0044] In some embodiments, the ultraviolet light irradiation treatment step includes: using a wavelength of 320–420 nm and a light density of 10–150 mJ / cm². 2 The ultraviolet light is applied from the anode side for 10–60 minutes. In this embodiment, when the ultraviolet light is applied from the anode side, the functional layers such as the anode, holes, and QD have minimal light loss. At the same time, to avoid the destructive effect of UV light energy on the organic materials in the hole functional layer, a longer wavelength and lower density light wave is used for irradiation.
[0045] In some embodiments, the ultraviolet light irradiation treatment step includes: using a wavelength of 250–320 nm and a light density of 100–200 mJ / cm². 2 The ultraviolet light is irradiated from the cathode side for 10–60 minutes. In this embodiment, when the ultraviolet light is irradiated from the cathode side, the metal cathode significantly reduces the UV light intensity. The light passes through the cathode layer and directly acts on the ETL layer, without affecting the materials of other functional layers such as holes. However, to avoid the influence of the light on the organic electron transport layer material, a wavelength of 250–320 nm and a light density of 100–200 mJ / cm² are used. 2 Ultraviolet light processing is more suitable.
[0046] In some embodiments, the metal oxide transport material is selected from at least one of ZnO, TiO2, Fe2O3, SnO2, and Ta2O3; these metal oxide materials have high electron mobility, and the excited electrons of O have good coordination with zinc in the QD shell layer.
[0047] In some embodiments, the metal oxide transport material is selected from at least one of ZnO, TiO2, Fe2O3, SnO2, and Ta2O3 doped with a metal element, wherein the metal element includes at least one of aluminum, magnesium, lithium, lanthanum, yttrium, manganese, gallium, iron, chromium, and cobalt. The metal oxide transport material in the embodiments of this application is doped with metal elements such as aluminum, magnesium, lithium, lanthanum, yttrium, manganese, gallium, iron, chromium, and cobalt, which is beneficial to further improve the electron transport and migration efficiency of the material.
[0048] In some specific embodiments, when the outer shell of the quantum dot material is ZnS, the wavelength of the ultraviolet light irradiation treatment is 250–355 nm, and the light density is 50–150 mJ / cm². 2 In this embodiment of the application, when the outer shell layer is ZnS, the ZnS bond energy is approximately 3.5 eV, and the ZnO bond energy is approximately 3.3 eV. This corresponds to a wavelength of 250–355 nm and an optical density of 50–150 mJ / cm². 2Under certain conditions, the transfer of bonding charges of electron transport materials such as ZnS and ZnO in the shell of quantum dot materials can be induced, resulting in a better coordination effect between the zinc element in the shell layer and the O element in the electron transport material, forming a complex of electron transport material and quantum dot material.
[0049] In some specific embodiments, when the outer shell of the quantum dot material is ZnSe, the wavelength of the ultraviolet light irradiation treatment is 280–375 nm, and the light density is 30–120 mJ / cm². 2 In this embodiment of the application, when the outer shell layer is ZnSe, the ZnSe bond energy is approximately 2.9 eV, and the ZnO bond energy is approximately 3.3 eV. The wavelength for ultraviolet light irradiation is 280–375 nm, and the light density is 30–120 mJ / cm². 2 Under certain conditions, the bonding charge of electron transport materials such as ZnSe and ZnO in the shell of quantum dot materials can be transferred, resulting in a better coordination effect between the zinc element in the shell layer and the O element in the electron transport material, forming a complex of electron transport material and quantum dot material.
[0050] In some specific embodiments, when the outer shell of the quantum dot material is ZnSeS, the wavelength of the ultraviolet light irradiation treatment is 250–375 nm, and the light density is 30–150 mJ / cm². 2 In this embodiment of the application, when the outer shell layer is ZnSeS, the bond energy of ZnSeS is approximately 2.7 eV, and the bond energy of ZnO is approximately 3.3 eV. The wavelength of ultraviolet light irradiation is 250–375 nm, and the light density is 30–150 mJ / cm². 2 Under certain conditions, the bonding charge of electron transport materials such as ZnSeS and ZnO in the shell of quantum dot materials can be transferred, resulting in a better coordination effect between the zinc element in the shell layer and the O element in the electron transport material, forming a complex of electron transport material and quantum dot material.
[0051] In some embodiments, the electron mobility of the organic transport material is greater than or equal to 10. -4 cm 2 / Vs, a high-mobility organic transport material, further ensures the efficiency of electron migration and transport in the transport layer, improves electron injection efficiency, and avoids the impact of charge accumulation on device lifetime.
[0052] In some embodiments, the organic transport material is selected from at least one of: 8-hydroxyquinoline-lithium (Alq3), aluminum octahydroxyquinoline, fullerene derivative PCBM, 3,5-bis(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole (BPT), and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi). These organic transport materials can achieve energy level modulation over a wider range, which is more conducive to modulating the energy levels of each functional layer of the device, thereby improving the stability and photoelectric conversion efficiency of the device.
[0053] In some embodiments, the thickness of the electron transport layer is 10–200 nm. In some specific embodiments, the thickness of the Nth sub-electron transport layer is 2–8 nm. This thickness meets device performance and structural requirements. In some specific embodiments, when the thickness of the electron transport layer is less than 80 nm, the duration of ultraviolet light irradiation is 15–45 minutes. In this application embodiment, when the electron transport layer thickness is less than 80 nm, light energy can penetrate relatively easily through the thinner material layer, and the irradiation time required to achieve the processing effect is shorter; a duration of 15–45 minutes is suitable for ultraviolet light irradiation. In other specific embodiments, when the electron transport layer thickness is greater than 80 nm, the duration of ultraviolet light irradiation is 30–90 minutes. In this application embodiment, when the electron transport layer thickness is greater than 80 nm, light energy is difficult to penetrate through the thicker material layer, and the irradiation time required to achieve the processing effect is longer; a duration of 30–90 minutes is suitable for ultraviolet light irradiation.
[0054] In some embodiments, the thickness of the quantum dot light-emitting layer is 8–100 nm. In some embodiments, the thickness of the hole transport layer is 10–150 nm. This thickness meets device performance and structural requirements.
[0055] In some embodiments, the outer shell layer of the quantum dot material has a thickness of 0.2 to 6.0 nm. This thickness ensures the stability of the inner quantum dot material and the carrier injection effect, while also ensuring the coordination effect of zinc in the outer shell layer with O in the metal oxide transport material.
[0056] In some embodiments, the cathode includes at least one metallic material selected from Mg, Ag, Al, and Ca, or an alloy of at least two of them. Under ultraviolet light irradiation, these cathode metallic materials have a good fusion effect with metal oxide electron transport materials, which can reduce the electron injection barrier and improve the efficiency of electron injection into optoelectronic devices.
[0057] In some specific embodiments, the fabrication of the light-emitting device in this application includes the following steps:
[0058] S50. Obtain a substrate with an anode deposited on it;
[0059] S60. A hole transport layer is grown on the anode surface;
[0060] S70. Next, a quantum dot luminescent layer is deposited on the hole transport layer;
[0061] S80. Then, an electron transport layer is deposited on the quantum dot luminescent layer;
[0062] S90. A cathode is deposited onto the electron transport layer by vapor deposition to obtain a light-emitting device;
[0063] S100. The light-emitting device is subjected to ultraviolet light irradiation treatment.
[0064] Specifically, in step S50, in order to obtain a high-quality zinc oxide nanomaterial film, the ITO substrate needs to undergo a pretreatment process. The basic and specific treatment steps include: cleaning the ITO conductive glass with a cleaning agent to initially remove the stains on the surface, then ultrasonically cleaning it for 20 minutes each in deionized water, acetone, anhydrous ethanol, and deionized water to remove impurities on the surface, and finally drying it with high-purity nitrogen gas to obtain the ITO cathode.
[0065] Specifically, in step S60, the step of growing the hole transport layer includes: depositing a prepared hole transport material solution on an ITO substrate using processes such as drop coating, spin coating, immersion, coating, printing, and vapor deposition; controlling the film thickness by adjusting the concentration of the solution, the deposition rate, and the deposition time; and then performing thermal annealing at an appropriate temperature.
[0066] Specifically, in step S70, the step of depositing the quantum dot luminescent layer on the hole transport layer includes: depositing a luminescent material solution of a certain concentration on the substrate on which the hole transport layer has been deposited, through processes such as drop coating, spin coating, immersion, coating, printing, and vapor deposition, and controlling the thickness of the luminescent layer, approximately 20 to 60 nm, by adjusting the concentration of the solution, the deposition rate, and the deposition time, and drying it at an appropriate temperature.
[0067] Specifically, in step S80, the step of depositing an electron transport layer on the quantum dot luminescent layer includes: the Nth sub-electron transport layer is a metal oxide transport material: on the substrate on which the quantum dot luminescent layer has been deposited, a metal oxide transport material solution of a certain concentration is deposited into a film through processes such as drop coating, spin coating, immersion, coating, printing, and evaporation. The thickness of the electron transport layer, approximately 20–60 nm, is controlled by adjusting the concentration of the solution, the deposition rate (preferably, the rotation speed is between 3000 and 5000 rpm), and the deposition time. Then, the film is annealed at 150°C to 200°C to completely remove the solvent. Sub-electron transport layers, such as organic transport materials or metal oxide transport materials, are then deposited on the surface of the Nth sub-electron transport layer.
[0068] Specifically, in step S90, the cathode preparation step includes: placing the substrate after the deposition of each functional layer in a vapor deposition chamber and thermally vapor-depositing a 60-100nm layer of metallic silver or aluminum as the cathode using a mask.
[0069] Specifically, in step S100, under an environment where the H2O content is less than 1 ppm and the temperature is 80–120°C, ultraviolet light with a wavelength of 250–420 nm and a light density of 10–300 mJ / cm² is used. 2 The optoelectronic device was vertically irradiated with ultraviolet light for 10–60 minutes.
[0070] In a further embodiment, the obtained QLED device is encapsulated. Encapsulation can be performed using conventional machine encapsulation or manual encapsulation. Preferably, the oxygen and water content in the encapsulation environment is both below 0.1 ppm to ensure device stability.
[0071] In other embodiments, the fabrication steps of the light-emitting device in this application may also adopt the fabrication sequence of the inverted device structure, wherein an electron transport layer, a quantum dot light-emitting layer, a hole transport layer, a hole injection layer, and an anode are sequentially fabricated on a substrate on which a cathode is deposited.
[0072] A second aspect of this application provides a light-emitting device, which is manufactured by the method described above.
[0073] The light-emitting device provided in the second aspect of this application employs a multi-layered composite structure for its electron transport layer, comprising both a metal oxide sub-transport layer with high electron mobility and an organic sub-transport layer with a wide range of energy level modulation. This allows the electron transport layer to simultaneously possess high electron mobility and flexibility in energy level matching, optimizing the electron-hole recombination efficiency within the light-emitting layer. Furthermore, after ultraviolet irradiation, electrons from the O in the metal oxide transport material of the Nth sub-electron transport layer are excited and form complexes with active metal elements such as Zn in the quantum dot light-emitting layer. Simultaneously, the metal oxide material exhibits good fusion with the cathode after ultraviolet excitation. This reduces internal physical structural defects and surface roughness within the electron transport layer, resulting in high electron transport mobility. Additionally, the interface between the quantum dot light-emitting layer and the electron transport layer is tightly bonded, leading to high electron injection efficiency, avoiding charge accumulation at the functional layer interface, and resulting in good device stability and a long lifespan.
[0074] In the embodiments of this application, the light-emitting device is not limited by the device structure; it can be a positive structure device or an inverse structure device.
[0075] In one embodiment, the positive-structure light-emitting device includes a stacked structure of an anode and a cathode disposed opposite each other, a light-emitting layer disposed between the anode and the cathode, and the anode being disposed on a substrate. Further, a hole functional layer such as a hole injection layer, a hole transport layer, and an electron blocking layer may be disposed between the anode and the light-emitting layer; and an electron functional layer such as an electron transport layer, an electron injection layer, and a hole blocking layer may be disposed between the cathode and the light-emitting layer, as shown in the attached figure. Figure 3 As shown. In some specific positive structure device embodiments, the light-emitting device includes a substrate, an anode disposed on the surface of the substrate, a hole transport layer disposed on the surface of the anode, a light-emitting layer disposed on the surface of the hole transport layer, an electron transport layer disposed on the surface of the light-emitting layer, and a cathode disposed on the surface of the electron transport layer.
[0076] In one embodiment, the inverted structure light-emitting device includes a stacked structure of an anode and a cathode disposed opposite each other, a light-emitting layer disposed between the anode and the cathode, and the cathode being disposed on a substrate. Further, a hole functional layer such as a hole injection layer, a hole transport layer, and an electron blocking layer may be disposed between the anode and the light-emitting layer; and an electron functional layer such as an electron transport layer, an electron injection layer, and a hole blocking layer may be disposed between the cathode and the light-emitting layer, as shown in the attached figure. Figure 4 As shown. In some embodiments of inverted structure devices, the light-emitting device includes a substrate, a cathode disposed on the surface of the substrate, an electron transport layer disposed on the surface of the cathode, a light-emitting layer disposed on the surface of the electron transport layer, a hole transport layer disposed on the surface of the light-emitting layer, and an anode disposed on the surface of the hole transport layer.
[0077] In some embodiments, the choice of substrate is not limited; a rigid substrate or a flexible substrate can be used. In some specific embodiments, the rigid substrate includes, but is not limited to, one or more of glass and metal foil. In some specific embodiments, the flexible substrate includes, but is not limited to, one or more of polyethylene terephthalate (PET), polyethylene terephthalate (PEN), polyetheretherketone (PEEK), polystyrene (PS), polyethersulfone (PES), polycarbonate (PC), polyarylate (PAT), polyarylate (PAR), polyimide (PI), polyvinyl chloride (PV), polyethylene (PE), polyvinylpyrrolidone (PVP), and textile fibers.
[0078] In some embodiments, the selection of the anode material is not limited and can be selected from doped metal oxides, including but not limited to one or more of indium-doped tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), and aluminum-doped magnesium oxide (AMO). It can also be selected from composite electrodes consisting of doped or undoped transparent metal oxides sandwiching a metal, including but not limited to one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2.
[0079] In some embodiments, the hole injection layer includes, but is not limited to, one or more of organic hole injection materials, doped or undoped transition metal oxides, and doped or undoped metal chalcogenides. In some specific embodiments, the organic hole injection materials include, but are not limited to, one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), copper phthalocyanine (CuPc), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), and 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzophenanthrene (HATCN). In some specific embodiments, the transition metal oxides include, but are not limited to, one or more of MoO3, VO2, WO3, CrO3, and CuO. In some specific embodiments, the metal chalcogenides include, but are not limited to, one or more of MoS2, MoSe2, WS2, WSe2, and CuS.
[0080] In some embodiments, the hole transport layer may be selected from organic materials and / or inorganic materials with hole transport capabilities. In some specific embodiments, organic materials with hole transport capabilities include, but are not limited to, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), polyvinylcarbazole (PVK), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4,4”-tris(carbazole-9-yl)triphenylamine (TCTA), 4,4'-bis(9-carbazole)biphenyl (CBP), N... One or more of N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD) and N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB). In some specific embodiments, the inorganic materials with hole transport capability include, but are not limited to, one or more of doped graphene, undoped graphene, C60, doped or undoped MoO3, VO2, WO3, CrO3, CuO, MoS2, MoSe2, WS2, WSe2, and CuS.
[0081] In some embodiments, the light-emitting layer includes the quantum dot material described in the above embodiments. The quantum dot material is a core-shell structured quantum dot material, and the outer shell of the quantum dot material contains zinc. In some specific embodiments, the outer shell of the quantum dot material includes at least one or an alloy material formed from at least two of ZnS, ZnSe, ZnTe, CdZnS, and ZnCdSe. In some embodiments, the particle size of the quantum dot material ranges from 2 to 10 nm. If the particle size is too small, the film-forming properties of the quantum dot material deteriorate, and the energy resonance transfer effect between quantum dot particles becomes significant, which is detrimental to the application of the material. If the particle size is too large, the quantum effect of the quantum dot material weakens, leading to a decrease in the photoelectric performance of the material.
[0082] In some embodiments, the electron transport layer is made of the electron transport layer with the above-described stacked composite structure.
[0083] In some embodiments, the cathode material can be one or more of various conductive carbon materials, conductive metal oxide materials, and metallic materials. In some specific embodiments, the conductive carbon material includes, but is not limited to, doped or undoped carbon nanotubes, doped or undoped graphene, doped or undoped graphene oxide, C60, graphite, carbon fibers, porous carbon, or mixtures thereof. In some specific embodiments, the conductive metal oxide material includes, but is not limited to, ITO, FTO, ATO, AZO, or mixtures thereof. In some specific embodiments, the metallic material includes, but is not limited to, Al, Ag, Cu, Mo, Au, or alloys thereof; the metallic material may have morphologies including, but is not limited to, dense thin films, nanowires, nanospheres, nanorods, nanocones, hollow nanospheres, or mixtures thereof; preferably, the cathode is Ag or Al.
[0084] To enable those skilled in the art to clearly understand the above-described implementation details and operations of this application, and to demonstrate the significant advancements in the performance of the light-emitting devices and their fabrication methods in the embodiments of this application, the following examples illustrate the above technical solutions.
[0085] Example 1
[0086] A light-emitting diode includes the following fabrication steps:
[0087] (1) Provide a substrate with an Al cathode deposited on it and perform a pretreatment to clean the substrate.
[0088] (2) Forming a composite electron transport layer on the Al cathode in step (1): Take a ZnO nanoparticle solution (concentration 30 mg / mL, solvent ethanol), spin-coat the ZnO nanoparticle solution onto the low electrode at 4000 rpm in a glove box (water and oxygen content less than 0.1 ppm), and anneal at 80℃ for 30 min to form a ZnO layer. Then, take an Alq3 solution (concentration 10 mg / mL, solvent dimethylformamide), spin-coat the Alq3 solution onto the ZnO layer at 1000 rpm, and anneal at 80℃ for 30 min to form an Alq3 layer.
[0089] (3) Forming a light-emitting layer on the electron transport layer: Take a CdSe / ZnS quantum dot solution (concentration of 30 mg / mL, solvent of n-octane), spin-coat the CdSe / ZnS quantum dot solution onto the electron transport layer at a speed of 3000 rpm in a glove box (water and oxygen content less than 0.1 ppm) to form a light-emitting layer.
[0090] (4) Forming a light-emitting layer on the hole transport layer: Take a CdSe / ZnS quantum dot solution (concentration of 30 mg / mL, solvent of n-octane), spin-coat the CdSe / ZnS quantum dot solution onto the hole transport layer at a speed of 3000 rpm in a glove box (water and oxygen content less than 0.1 ppm) to form a light-emitting layer.
[0091] (5) Forming a hole transport layer on the light-emitting layer: Under an electric field, TFB solution (concentration of 8 mg / mL, solvent of chlorobenzene) is spin-coated onto the light-emitting layer. After spin-coating at 3000 rpm for 30 s, the layer is annealed at 80℃ for 30 min to form a hole transport layer. The direction of the electric field is perpendicular to the anode and toward the hole transport layer, and the electric field strength is 104 V / cm.
[0092] (6) Forming a hole injection layer on the hole transport layer: Under an electric field, spin-coating PEDOT:PSS solution onto the hole transport layer, spin-coating at 5000 rpm for 40 s, and then annealing at 150℃ for 15 min to form a hole injection layer; wherein, the direction of the electric field is perpendicular to the anode and toward the hole injection layer, and the electric field strength is 104 V / cm.
[0093] (7) Form an ITO anode on the hole injection layer.
[0094] (8) The prepared device was subjected to UV treatment. Under conditions where the H2O content was less than 1 ppm and the temperature was 100°C, the device was irradiated vertically from the Al electrode side. The UV wavelength was 250 nm and the intensity was 200 mJ / cm. 2 UV time 30min.
[0095] Example 2
[0096] A light-emitting diode, the difference between its preparation steps and those of Example 1 is that: in step (2), an organic electron transport layer is prepared using PCBM.
[0097] Example 3
[0098] A light-emitting diode, the difference between its preparation steps and those of Example 1 is that: in step (2), ZnMgO is used to prepare an inorganic electron transport layer.
[0099] Example 4
[0100] A light-emitting diode, the difference between its preparation steps and those of Example 1 is that: in step (2), Alq3+ZnO (particle size of 5.5nm)+ZnO (particle size of 3nm) is used.
[0101] Example 5
[0102] A light-emitting diode (LED) differs from the one in Example 1 in that: CdZnSe / ZnSe is used in step (3). In step (8), the ultraviolet irradiation conditions are: UV wavelength 320nm, intensity 300mJ / cm². 2 The UV light was vertically irradiated onto the light-emitting layer for 30 minutes.
[0103] Example 6
[0104] A light-emitting diode (LED) is prepared in a manner different from that in Example 1, CdZnSe / ZnSeS is used in step (3). In step (8), the ultraviolet irradiation conditions are: 340 nm, intensity 300 mJ / cm². 2 The UV light was vertically irradiated onto the light-emitting layer for 30 minutes.
[0105] Comparative Example 1
[0106] A light-emitting diode, the difference between its preparation steps and those of Example 1 is that it does not undergo UV treatment in step (8).
[0107] Comparative Example 2
[0108] A light-emitting diode, the difference in its fabrication steps from that in Example 1 is that the electron transport layer in step (2) contains only a ZnO metal oxide layer.
[0109] Comparative Example 3
[0110] A light-emitting diode, the difference between its preparation steps and those of Example 1 is that the electron transport layer in step (2) contains only an Alq3 organic transport layer.
[0111] Furthermore, to verify the progressiveness of the embodiments of this application, the following performance tests were conducted on Embodiments 1-6 and Comparative Examples 1-3. The test indicators and methods are as follows, and the test results are shown in Table 1 and Appendix. Figures 5-7 As shown:
[0112] (1) Construct the current density-voltage (JV) curve
[0113] The efficiency test system was built using a LabVIEW-controlled QE PRO spectrometer, Keithley 2400, and Keithley 6485 in an environment with room temperature and air humidity of 30%-60%. The system measured parameters such as voltage and current and constructed JV curves.
[0114] (2) External quantum efficiency (EQE):
[0115] The ratio of electron-hole pairs injected into a quantum dot to emitted photons, expressed as a percentage (%), is an important parameter for evaluating the quality of electroluminescent devices. It can be measured using an EQE optical testing instrument. The specific calculation formula is as follows:
[0116]
[0117] In the formula, ηe is the optical output coupling efficiency, ηr is the ratio of recombination carriers to injected carriers, χ is the ratio of the number of excitons generating photons to the total number of excitons, KR is the radiative process rate, and KNR is the non-radiative process rate. Test conditions: conducted at room temperature with an air humidity of 30–60%.
[0118] (3) Constructing the luminance-voltage (LV) curve
[0119] Luminance (L) is the ratio (cd / m2) of the luminous flux of the emitting surface in a specified direction to the area of the luminous flux perpendicular to the specified direction. Measurements were taken using a LabVIEW-controlled, calibrated linear silicon photodiode system, PDB-C613. The device luminance was calculated by combining spectral and visual functions, and an LV curve was constructed based on the variation of luminance with voltage.
[0120] (4) Life test
[0121] In the following embodiments, the lifetime test was performed using the constant current method at a constant 50 mA / cm². 2 Driven by current, a silicon photonics system was used to test the brightness change of the device. The time (LT95) for the device brightness to decay from its highest point to 95% of its highest brightness was recorded. Then, the device lifetime of 1000 nits (LT95S) was extrapolated using an empirical formula.
[0122] 1000nit LT95=(L Max / 1000) 1.7 ×LT95;
[0123] This method facilitates the comparison of the lifetime of devices with different brightness levels and has wide applications in practical optoelectronic devices.
[0124] Table 1
[0125]
[0126] The test results in Table 1 of Examples 1-6 and Comparative Examples 1-3, and the appendices to Examples 1 (S1), 4 (S2), 1 (S3), and 2 (S4) Figure 5 Efficiency curve (horizontal axis: voltage, vertical axis: external quantum efficiency), attached Figure 6 Current density-voltage curve (horizontal axis: voltage, vertical axis: current density), attached. Figure 7As can be seen from the brightness curves (the horizontal axis represents time and the vertical axis represents brightness), the devices of Examples 1 to 6 of this application, after UV treatment, have better luminous efficiency and longer luminous lifetime compared to the devices of Comparative Examples 1 to 3.
[0127] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for fabricating a light-emitting device, characterized in that, Includes the following steps: Obtain a substrate with a deposited cathode; A first sub-electron transport layer to an Nth sub-electron transport layer are sequentially prepared on the cathode surface away from the substrate to form an electron transport layer. A quantum dot light-emitting layer and an anode are sequentially fabricated on the surface of the Nth sub-electron transport layer away from the cathode to obtain a light-emitting device; The light-emitting device is subjected to ultraviolet light irradiation treatment; Wherein, at least one sub-electron transport layer in the electron transport layer includes an organic transport material, and at least the Nth sub-electron transport layer includes a metal oxide transport material, where N is a positive integer greater than or equal to 2; The quantum dot luminescent layer includes a core-shell structured quantum dot material, and the outer shell of the quantum dot material contains zinc. The ultraviolet light irradiation treatment causes the electrons of the O in the metal oxide transport material in the Nth sub-electron transport layer to be excited and form a complex with the zinc element in the outer shell of the quantum dot light-emitting layer.
2. The method for fabricating a light-emitting device as described in claim 1, characterized in that, In the electron transport layer, the first sub-electron transport layer and the Nth sub-electron transport layer each independently contain metal oxide transport materials, where N is a positive integer greater than or equal to 3 and less than or equal to 9; And / or, after preparing the quantum dot light-emitting layer, the method further includes the steps of: preparing a hole transport layer on the surface of the quantum dot light-emitting layer opposite to the electron transport layer, and preparing the anode on the surface of the hole transport layer opposite to the quantum dot light-emitting layer.
3. The method for fabricating the light-emitting device as described in claim 2, characterized in that, The particle size of the metal oxide transport material in the Nth sub-electron transport layer is 2~4 nm; And / or, the electron transport layer includes at least one sub-electron transport layer of metal oxide transport material with a particle size of 4~8 nm.
4. The method for fabricating the light-emitting device according to any one of claims 1 to 3, characterized in that, The outer shell of the quantum dot material includes at least one or an alloy of at least two of ZnS, ZnSe, ZnTe, CdZnS, and ZnCdSe.
5. The method for fabricating a light-emitting device as described in claim 1, characterized in that, The ultraviolet light irradiation treatment step includes: using ultraviolet light with a wavelength of 250~420 nm and a light density of 10~300 mJ / cm². 2 Under the conditions described above, the light-emitting device is irradiated for 10-60 minutes; And / or, the conditions for the ultraviolet irradiation treatment further include: carrying out the treatment in an environment where the H2O content is less than 1 ppm and the temperature is 80~120 ℃.
6. The method for fabricating a light-emitting device as described in claim 5, characterized in that, The ultraviolet light irradiation treatment step includes: using a wavelength of 320~420 nm and a light density of 10~150 mJ / cm². 2 The ultraviolet light waves are irradiated from the anode side for 10~60 min; Alternatively, the ultraviolet light irradiation treatment step includes: using a wavelength of 250~320 nm and a light density of 100~200 mJ / cm². 2 The ultraviolet light is irradiated from the cathode side for 10 to 60 minutes.
7. The method for fabricating the light-emitting device according to any one of claims 1-3 and 5-6, characterized in that, The metal oxide transport material is selected from at least one of ZnO, TiO2, Fe2O3, SnO2, and Ta2O3; And / or, the metal oxide transport material is selected from at least one of ZnO, TiO2, Fe2O3, SnO2, and Ta2O3 doped with a metal element, wherein the metal element includes at least one of aluminum, magnesium, lithium, lanthanum, yttrium, manganese, gallium, iron, chromium, and cobalt.
8. The method for fabricating a light-emitting device as described in claim 7, characterized in that, The electron mobility of the organic transport material is greater than or equal to 10. -4 cm 2 / Vs; And / or, the organic transport material is selected from at least one of: 8-hydroxyquinoline-lithium, octahydroxyquinoline aluminum, fullerene derivatives, 3,5-bis(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole, and 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene.
9. The method for fabricating a light-emitting device as described in claim 2, characterized in that, The thickness of the electron transport layer is 10~200 nm; And / or, the thickness of the quantum dot light-emitting layer is 8~100 nm; And / or, the outer shell layer thickness of the quantum dot material is 0.2~6.0 nm; And / or, the thickness of the hole transport layer is 10~150 nm; And / or, the cathode comprises at least one metallic material selected from Mg, Ag, Al, and Ca, or an alloy of at least two of them.
10. The method for fabricating a light-emitting device as described in claim 9, characterized in that, When ultraviolet light is irradiated from the cathode side and the thickness of the electron transport layer is less than 80 nm, the duration of the ultraviolet light irradiation treatment is 15 minutes to 45 minutes. Alternatively, when ultraviolet light is irradiated from the cathode side and the thickness of the electron transport layer is greater than 80 nm, the duration of the ultraviolet irradiation treatment is 30 to 90 minutes.
11. A light-emitting device, characterized in that, The light-emitting device is prepared by the method described in any one of claims 1 to 10.
Citation Information
Patent Citations
Quantum dot electroluminescent device and display
CN108963087A
Preparation method of quantum dot light-emitting diode and quantum dot ink
CN111384268A